Tropical biologists, local people and conservation: new opportunities for collaboration - Sheil, Douglas; Lawrence, A. (2004)
Tropical biologists need help. Examples show that local people can be trained to be effective parataxonomists, greatly assisting efforts to document and assess tropical biodiversity. Local collaborations also offer promising ways with which to improve natural resource management and conservation. However, for several reasons, most biologists remain slow to approve and implement these approaches. The challenges and potentials need evaluation and neglect means that opportunities are being missed. The authors consider experiences of local collaborations and discuss obstacles to their wider implementation. They urge tropical biologists to recognize and embrace the opportunities provided by working with local people.